The application and influence of online marketing in brand communication: A case study of Starbucks - Xu An (SHS Web of Conferences)
In recent years, with the rapid development of network technology and the improvement of people’s living standards, people use the Internet more and more frequently, and use the Internet to study, work and live. The Internet has become a popular sales channel, and more and more new brands hope to expand operation channels through the Internet platform to enhance customer stickiness and achieve higher brand revenue. Nowadays, online marketing has greatly increased the total revenue of various companies and brought faster economic development to society. Starbucks, a famous coffee brand, has created a network marketing model that conforms to its own brand characteristics and realized the digital transformation of its brand through rational use of network marketing means. Through case analysis, this paper mainly studies the network marketing channels of Starbucks and the advantages it brings, but there are also disadvantages such as user groups, user stickiness and human resource redistribution.